2005
DOI: 10.1097/01.mlg.0000181463.16591.a7
|View full text |Cite
|
Sign up to set email alerts
|

Olivocochlear Activity and Temporary Threshold Shift‐Susceptibility in Humans

Abstract: 1) Measurement of CS of DPOAE using an extensive measurement paradigm revealed good test-retest repeatability, confirming the reliability of this audiologic tool. 2) CS of DPOAE does not predict individual susceptibility to mild TTS induced by impulse noise in humans. Possible explanations for the missing association are discussed. Future perspectives include longitudinal studies to further elucidate the association between medial olivocochlear bundle-activity and permanent threshold shift in humans. The goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
3
20
1
2
Order By: Relevance
“…Wagner et al (2008) calculated MOC efferent activity as (a) the mean of level changes (negative and positive values combined) for each subject upon contralateral stimulation, (b) the mean of all level changes in absolute value irrespective of whether the MOC effect was a reduction or enhancement of OAE amplitude, and (c) the difference between the highest and lowest suppression value (range of suppression) for each subject. Their results suggest good repeatability for the two DPOAE protocols, with the exception of range of suppression in protocol A, and were consistent with their previous studies using similar methods (Wagner et al, 2005;Wagner, Heppelmann, Müller, Janssen, & Zenner, 2007). Wagner et al's (2008) estimation of the MOC reflex, however, was compromised for at least two reasons.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Wagner et al (2008) calculated MOC efferent activity as (a) the mean of level changes (negative and positive values combined) for each subject upon contralateral stimulation, (b) the mean of all level changes in absolute value irrespective of whether the MOC effect was a reduction or enhancement of OAE amplitude, and (c) the difference between the highest and lowest suppression value (range of suppression) for each subject. Their results suggest good repeatability for the two DPOAE protocols, with the exception of range of suppression in protocol A, and were consistent with their previous studies using similar methods (Wagner et al, 2005;Wagner, Heppelmann, Müller, Janssen, & Zenner, 2007). Wagner et al's (2008) estimation of the MOC reflex, however, was compromised for at least two reasons.…”
supporting
confidence: 78%
“…Present results cannot be directly compared with previous studies that used DPOAEs without controlling for fine structure (Kumar et al, 2013;Wagner et al, 2005Wagner et al, , 2007Wagner et al, , 2008. Using click-evoked OAEs, de Boer and Thornton (2008) reported a mean increase in the MOC reflex of 0.63 dB on Day 4 and 0.78 dB on Day 5 when they implemented a 5-day training regimen to improve listening in adults with normal hearing.…”
Section: Comparison With Literaturecontrasting
confidence: 52%
“…There are also several other papers that show individual MOCR effects across subjects from which MOCR strength distributions might be calculated (Micheyl et al 1995;Micheyl and Collet 1996;Kumar and Vanaja 2004;Muller et al 2005;Wagner et al 2005Wagner et al , 2007. A major drawback of the De Ceulaer et al distribution is that no information was provided on the amount of measurement error in the data.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Although there are considerable data showing that there is a medial olivocochlear reflex (MOCR) in humans, most studies show averages and only a few show MOCR effects across individual subjects (Micheyl et al 1995;Micheyl and Collet 1996;De Ceulaer et al 2001;Wagner et al 2005). De Ceulaer et al (2001) presented the first measured distribution of MOCR strengths across individuals using otoacoustic emissions (OAEs).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1930, a considerable number of studies were unsuccessful in reaching that goal. Among the audiological methods used were discrimination of loudness, temporal sound integration ability, speech discrimination in background noise, and stapedial reflex (SR) measurement [overview in Wagner et al, 2005]. A breakthrough in our understanding of individual noise vulnerability emerged in the 1980s when studies demonstrated in different mammal species that the neural activity of the medial olivocochlear efferents (MOC) can exert a noise-protective role on the cochlea [Rajan and Johnstone, 1983].…”
Section: Introductionmentioning
confidence: 99%